การแสดงออกของยีนที่ควบคุมการแปลรหัสในซิโนวิโอไซต์จากผู้ป่วยโรคข้อเข่าเสื่อม - ธารนภ สุภัคสถาพรพันธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Knee osteoarthritis (knee OA) is caused by degradation of articular cartilage partly due to gene expression in synoviocytes. From microarray data, bioinformatics analysis was performed to compare gene expression between synovial membrane from knee OA patients (n=10) and from control group (n=9). The result showed that at least 4,816 genes were statistically significantly different. Genes involved in transcriptional and translational processes were investigated. ATF3, DPH5, eIF4G2 and SBP2 genes were selected to study the gene expression with real-time PCR and validate the microarray result. RNA samples were extracted from fresh synovial fluid and from cultured synoviocytes. These samples were obtained from 10 knee OA patients and 5 controls. The real-time PCR result revealed that the gene expression of eIF4G2, DPH5 and SBP2 from synovial fluid were statistically different between the two groups (P < 0.05) and also had higher expression level in the patients, but eIF4G2 and SBP2 results contradicted to the data from microarray. ATF3 expression levels from synovial fluid were not significantly different between the two groups (P > 0.05). However ATF3 from cultured cells was statistically different; the patients had a higher level of expression (P < 0.01) as opposed to lower level in the microarray result. While DPH5, eIF4G2 and SBP2 from cultured synoviocytes showed no significant difference (P > 0.05). The inconsistent results from the real-time PCR from synovial fluid and cultured synoviocytes as well as microarray, may arise from the heterogeneity of the samples and possible false positive result in microarray.